ACQUISITION AND STRATEGIC USE OF COMPETITIVE INTELLIGENCE - Yap, Ching Seng; Abdul Rashid, Md Zabid (Malaysian Journal of Library and Information Science, 2017)
This study investigates the current status of competitive intelligence (CI) practices in Malaysia, and how managers acquire and use CI from various sources. Data are collected through mail questionnaire survey from 123 companies listed on Bursa Malaysia. More than half of the surveyed companies have a formal CI unit in their organisation. These units are mostly located within the marketing or market research or corporate planning department and has been established from 5 to 9 years. On average, 2 to 5 full-time personnel are assigned to take charge of CI activities. The top three sources managers acquire CI are newspapers and periodicals, the Internet and extranets, and customers. Whereas, the top three sources where CI is used in strategic decision making are customers, competitors, and newspapers and periodicals. In terms of source category, while the frequency of acquiring CI is higher from external impersonal sources, the frequency of using external and personal sources in strategic decision making is significantly higher than internal and impersonal sources. The article includes implications and recommendations for future studies